Estimation of Genetic and Phenotypic Parameters for Growth Traits in a Clonal Seed Orchard of Pinus kesiya in Malawi. (26th November 2013) - Missanjo, Edward; Kamanga-Thole, Gift; Manda, Vidah
Abstract : Genetic and phenotypic parameters for height, diameter at breast height (dbh), and volume were estimated for Pinus kesiya Royle ex Gordon clonal seed orchard in Malawi using an ASReml program, fitting an individual tree model. The data were from 88 clones assessed at 18, 23, 30, 35, and 40 years of age. Heritability estimates for height, dbh, and volume were moderate to high ranging from 0.19 to 0.54, from 0.14 to 0.53, and from 0.20 to 0.59,  respectively, suggesting a strong genetic control of the traits at the individual level, among families, and within families. The genetic and phenotypic correlations between the growth traits were significantly high and ranged from 0.69 to 0.97 and from 0.60 to 0.95, respectively. This suggests the possibility of indirect selection in trait with direct selection in another trait. The predicted genetic gains showed that the optimal rotational age of the Pinus kesiya clonal seed orchard is 30 years; therefore, it is recommended to establish a new Pinus kesiya clonal seed orchard. However, selective harvest of clones with high breeding values in the old seed orchard should be considered so that the best parents in the old orchard can continue to contribute until the new orchard is well established.